2020
DOI: 10.2139/ssrn.3704136
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Predicted Impacts of Covid-19 Prophylactic Measures in Terms of Lives Saved Rather than Deaths is More Effective for Older People

Abstract: This paper contributes to the literature on public health communication by studying how the framing of a message relaying the forecast impact of COVID-19 prevention measures affects compliance behaviour amongst both the young and old. A representative sample of survey respondents in the UK and US, along with selected respondents in Italy, were presented with forecasts for the number of deaths from COVID-19 in their countries with and without public adherence to various preventive behaviours. We experimentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
2
0
0
Order By: Relevance
“…Even when the events affect people in a very personal and direct way, the impact on people’s preferences is still mediated by framing effects. Our results, which confirm what others (e.g., Biroli et al 2020; Hameleers 2020) have also suggested, imply that governments should carefully nuance their public communication about risks and losses, being them human or financial. Second, we document a not‐so‐invariant perception of risks by people differently affected by the effects of the pandemic – something equally relevant for public communication.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Even when the events affect people in a very personal and direct way, the impact on people’s preferences is still mediated by framing effects. Our results, which confirm what others (e.g., Biroli et al 2020; Hameleers 2020) have also suggested, imply that governments should carefully nuance their public communication about risks and losses, being them human or financial. Second, we document a not‐so‐invariant perception of risks by people differently affected by the effects of the pandemic – something equally relevant for public communication.…”
Section: Discussionsupporting
confidence: 91%
“…While the interaction coefficient between age and the treatment condition does not pass the significance test, this tendency seems to be in line with research suggesting that older age cohorts are generally more sensitive to heuristics (Kim et al 2005; Mata et al 2011; contra Best and Charness 2015) – including the framing of the health consequences of the pandemic (Biroli et al 2020) – than younger cohorts.…”
Section: Resultssupporting
confidence: 75%